2018
DOI: 10.1016/j.jsps.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytochrome P450 enzymes by thymoquinone in human liver microsomes

Abstract: The aim of the present study was to investigate the potential effect of thymoquinone (TQ) on the metabolic activity of four major drug metabolizing enzymes in human liver microsomes, namely cytochrome P450 (CYP) 1A2, CYP2C9, CYP2D6 and CYP3A4. The inhibition of CYP enzymatic activities by TQ was evaluated by incubating typical substrates (phenacetin for CYP1A2, tolbutamide for CYP2C9, dextromethorphan for CYP2D6, and testosterone for CYP3A4) with human liver microsomes and NADPH in the absence or presence of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
1
25
0
1
Order By: Relevance
“…Earlier studies have described that herbs like N. Sativa and T. Foenum-graecum possibly will inhibit the activity of CYP3A ( Albassam et al, 2018 , Al-Jenoobi et al, 2014a , Al-Jenoobi et al, 2014b , Alkharfy et al, 2013 , Korashy et al, 2015 ). The losartan in general metabolized by CYP3A4 and CYP2C9, and hence, we proposed that the herb-losartan interaction could happen owing to the effects of investigated herbs on the activity of these enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have described that herbs like N. Sativa and T. Foenum-graecum possibly will inhibit the activity of CYP3A ( Albassam et al, 2018 , Al-Jenoobi et al, 2014a , Al-Jenoobi et al, 2014b , Alkharfy et al, 2013 , Korashy et al, 2015 ). The losartan in general metabolized by CYP3A4 and CYP2C9, and hence, we proposed that the herb-losartan interaction could happen owing to the effects of investigated herbs on the activity of these enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Nigella sativa , (also named as black seed and black cumin; Family; Ranunculaceae), has been revealed to have antihypertensive properties in humans as well as in animals ( Ahmad et al, 2013 , Fallah Huseini et al, 2013 , Khattab and Nagi, 2007 ). Black seed has been utilized for long times for medicative and cooking purposes all over India, Middle East, and Northern Africa ( Albassam et al, 2018 ). Thymoquinone and polyphenols are the main chemical constituent found in N. Sativa seed oil ( Jaarin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main active constituents in N. sativa seeds and oil is thymoquinone. Thymoquinone has shown to bind to human α(1)-acid glycoprotein in the plasma [111] and inhibit CYP2C9 > 2D6 > 1A2 > 3A4 liver enzymes [112]. In hypertensive rats, N. sativa + alompidine showed greater reduction in blood pressure and heart rate than N. sativa alone, but no effect on alompidine pharmacokinetics (C max , AUC 0-t , K el , and terminal half-life) [113].…”
Section: Nigella Sativa Pharmacokineticsmentioning
confidence: 99%
“…Table 3 discusses some of the chemo-modulating effects of TQ in combination with known anticancer drugs. However, as with any other drug, further studies should be done to investigate the standardization of TQ administration when used with cancer drugs, as literature showed that CYP1A2, CYP2C9, CYP2D6 and CYP3A4 were subject to inhibition by TQ, hinting at various potential drug–drug interactions [ 142 ].…”
Section: Anticancer Effects Of Thymoquinonementioning
confidence: 99%